IMPLEMENTASI UPAYA KESEHATAN MASYARAKAT (UKM) SEKUNDER DI BALKESMAS WILAYAH MAGELANG - Shabika Imany Putri Wiguna; Sutopo Patria Jati; Wulan Kusumastuti (Jurnal Kesehatan Masyarakat (Undip), 2021)
The establishment of Public Health Center (Balkesmas) organization in Central Java is based on Central Java Governor Regulation Number. 99 of 2016. The Public Health Center (Balkesmas) provides public health services in the form of second-tier Public Health Efforts (UKM). In the implementation, a record related to the referral of UKM secondary was not recorded well and the regency/city has less involvement as a referral of UKM secondary in Public Health Center (Balkesmas) of Magelang region. Therefore, in an effort to implement referral of UKM secondary effectively and efficiently, Balkesmas of Magelang region need to pay attention of availability of resources in the organization, interpretation and application. This study aims to analyze the implementation referral of UKM secondary in Balkesmas of Magelang region based on Charles O Jones theory which consists of organization, interpretation and application. The research used a descriptive qualitative method with indepth interview and literature study toward selected informants based on purposive sampling criteria. The results of this study indicate that the Implementation Referral of UKM Secondary In Balkesmas of Magelang region has not run optimally yet due to several obstacles. Human resources are not placed according to their competence, Lack of understood about referral of UKM and the underlying guidelines, the implementation was not based on guidelines and technical instructions. Thus, it is recommended for the Central Java Provincial Health Service to carry out the fulfillment of human resources according to the required competencies and provide socialization to implementor about referral of UKM, and for Balkesmas of Magelang region to implement referral of UKM based on guidelines and technical instructions and provide socialization about referral of UKM to the regency / city of Balkesmas of Magelang region.